PENGARUH KOMPENSASI, PROMOSI JABATAN DAN DISIPLIN KERJA TERHADAP KINERJA APARATUR SIPIL NEGARA (ASN) DI SEKRETARIAT DAERAH KABUPATEN SITUBONDO - Bariatul Qomariah; Edy Kusnadi Hamdun; Lita Permata Sari (Fakultas Ekonomi dan Bisnis, 2025)
This study aims (1) to determine the partial effect of compensation, job promotion and work discipline on ASN performance (2) to determine the simultaneous effect of compensation, job promotion and work discipline on ASN performance (3) to determine compensation, promotion and discipline work that has a dominant influence on the performance of ASN. The method used is multiple linear regression analysis, t test, f test, dominant test and coefficient of determination. The result of this research is multiple linear regression equation Y = -8,300E-17 + 0.404X1 + 0.270X2 + 0.257X3 + e. The results of the t-test of the compensation variable are tcount 3,580 > ttable 2,004. The variable of job promotion is tcount 2,335 > ttable 2,004. The variable of work discipline is tcount 2.189 > ttable 2.004. Then the variables of compensation, promotion and work discipline partially affect the performance of ASN. The results of the F test show the value of Fcount 10.236 > Ftable 2.78, so compensation, promotion and work discipline simultaneously affect the performance of ASN. The dominant test results for compensation variables are 3.580, job promotions are 2.335 and work discipline are 2.189, then the value of the compensation variable is greater than the variable of job promotion and work discipline, which is 3.580 thus, the compensation variable that has a dominant influence on ASN performance.